Екзистеншйна проблема самотності у новелістиці Марка Черемшини - Лях, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the existential problem of solitude in the short stories by Marko Cheremshyna. The phenomenon of solitude is comprehended in external and internal dimensions. The internal solitude plays a special role in the Cheremshyna’s creative work. It is given rise by open transcending character of human being.